Efektivitas Media Instagram Dalam Branding Fakultas Ilmu Komunikasi Universitas Garut - Chotijah Fanaqi; Muhamad Azi Zulhakim; Fitri Nadia Komalasari (Jurnal Digital Media dan Relationship, 2020)
Social media is media that is used to publish content such as profiles, activities, or even user opinions as well as media that provide space for communication and interaction in social networks in cyberspace. This research is a quantitative research with an associative approach. The population in this study was the new students of the Faculty of Communication at the University of Garut in 2019, with a sample of 70 students, with proportional random sampling. Data collection techniques using a questionnaire. Theory of this study used the Uses and Gratification Theory. The results showed that the curiosity and intensity motives had significant and significant influence on satisfaction on the effectiveness of Instagram media in the UNIGA FIKOM Branding of New Student Admission Interests. This is evidenced by the results of several tests that have been conducted, whether testing is stimulant or partial, where the results of each test explain that there is an influence of motives on satisfaction.